Elastic buckling analysis of uniaxially compressed CCCC stiffened isotropic plates - Ibeabuchi, Victor; Ibearugbulem, Owus; Ezeah, Chukwunonye; Ugwu, Onuegbu (Zielona Góra: Uniwersytet Zielonogórski)
This paper reports a research study that investigated buckling of stiffened rectangular isotropic plates elastically restrained along all the edges (CCCC) under uniaxial in-plane load, using the work principle approach. The stiffeners were assumed to be rigidly connected to the plate. Analyses for critical buckling of stiffened plates were carried out by varying parameters, such as the number of stiffeners, stiffness properties and aspect ratios.
Keywords: buckling; governing equation; polynomial function; uniaxially stiffened plate; work principle method